Influence of relativistic electron beam divergence on angular characteristics of PXR and DTR generated in a single-crystal plate in Bragg scattering geometry - Blazhevich, S.V.; Boltenko, Yu.A.; Koskova, T.V.; Mazilov, A.A.; Noskov, A.V. (Вопросы атомной науки и техники, 2015)
A dynamical theory of coherent X-ray radiation generated in a single-crystal target by the finite divergence beam of relativistic electrons has been developed in the scattering Bragg geometry. Coherent X-ray emission is considered in general case of asymmetric reflection for electron Coulomb field in the form of two emission mechanism contributions: parametric X-ray radiation (PXR) and diffracted transition radiation (DTR). The method of averaging radiation cross section over the angular electrons distribution is used. The influence of electron beam divergence on both spectral and angular characteristics of coherent radiation has been studied. The significant difference of the effects of electron beam divergence in PXR and DTR is shown. The possibilities of practical use of DTR from a single-crystal target for indication of beam divergence of ultrarelativistic electrons are investigated. Розвинено динамічну теорію когерентного рентгенівського випромінювання, генерованого в геометрії розсіяння Брегга в монокристалічній мішені пучком релятивістських електронів кінцевої розбіжності. Когерентне рентгенівське випромінювання розглядається в загальному випадку асиметричного відбиття кулонівського поля електрона у вигляді внесків двох механізмів випромінювання: параметричного (ПРВ) і дифрагованого перехідного (ДПВ). Використовується усереднення поперечного перерізу випромінювання за кутовим розподілом електронів. Вивчено вплив розбіжності електронного пучка на спектральні і кутові характеристики когерентного випромінювання. Показано значну відмінність впливу розбіжності електронного пучка на ПРВ і ДПВ. Досліджено можливість практичного використання ДПВ з монокристалічної мішені для індикації розбіжності пучка ультрарелятивістських електронів. Развита динамическая теория когерентного рентгеновского излучения, генерированного в геометрии рассеяния Брэгга в монокристаллической мишени пучком релятивистских электронов конечной расходимости. Когерентное рентгеновское излучение рассматривается в общем случае асимметричного отражения кулоновского поля электрона в виде вкладов двух механизмов излучения: параметрического (ПРИ) и дифрагированного переходного (ДПИ). Используется усреднение поперечного сечения излучения по угловому распределению электронов. Изучено влияние расходимости электронного пучка на спектральные и угловые характеристики когерентного излучения. Показано значительное отличие влияния расходимости электронного пучка на ПРИ и ДПИ. Исследована возможность практического использования ДПИ из монокристаллической мишени для индикации расходимости пучка ультрарелятивистских электронов.